Riesgo cardiovascular en pacientes hipertensos que acuden a Consulta Externa de Cardiología en el Hospital en el Hospital General Teófilo Dávila de Machala. - Poma Ramón, Luis Alejandro (2016)
Cardiovascular diseases are the leading cause of disability and the premature death worldwide, contributing substantially to the rising costs of health care. To initiate preventive actions or clinical treatments of these disease, we should be guided by Cardiovascular Risk, the very same which can be established using various scales such as the Framingham study, which reveals the likelihood of suffering from an acute cardiovascular event in a given period (10 years). This thesis aims to determine Cardiovascular Risk in Hypertensive patients treated in the outpatient cardiology unit at the Teófilo Dávila General Hospital in Machala during the period between January and June 2016, to catalogue the risk within the catagories low risk, moderate risk, high risk and very high risk and similarly classify them according to age and gender, which will allow us to analyze the type of intervention that is required. This is a descriptive study that involving 85 patients (735 universe). Results: 43% of the patients (37 cases) have a Moderate Cardiovascular Risk, i.e. have a 5 to 9% probability of suffering an acute myocardial infarction within 10 years, these are mainly aged between 55 to 74 years and have a similar distribution with respect to gender. Low Cardiovascular Risk takes second place with 41% of patients (35 cases) and a corresponding probability of 5% of suffering an acute coronary event within 10 years, these are principally 35 to 54 years old and of female gender. A minority of the population exhibits a High or Very High Cardiovascular Risk with 15% (12 cases) and 1% (1 case) respectively. The study concluded that 84% of the population requires Primary Prevention; which aims to prevent or delay the onset of the disease by focussing on the control of the known cardiovascular risk factors. While 16% indispensably precise secondary prevention; a change of lifestyle and further application of pharmacological treatments. Keywords: Cardiovascular Risks, Cardiovascular Disease.